Novel supramolecular networks based on PEG and PEDOT cross-linked polyrotaxanes as electrical conductive materials. (May 2019) - Resmerita, Ana-Maria; Asandulesa, Mihai; Bulai, Georgiana; Farcas, Aurica
Graphical abstract: Highlights: Supramolecular networks based on PEG and PEDOT cross-linked polyrotaxanes. Their chemical structures were investigated by ATR-FT-IR and WAXS analyses. The dielectric permittivity proves the presence of the PEDOT in the matrix. The dielectric peak of secondary β-relaxation exhibits a narrower distribution. Electrical conductivity is a thermally activated process. Abstract: New supramolecular networks were synthesized by cross-linking reaction of polyethylene glycol (PEG) polyrotaxane with a 10 wt% of poly(3, 4-ethylenedioxythiophene) (PEDOT) polyrotaxanes. For comparison purpose, a cross-linked material of PEG polyrotaxane with PEDOT non-rotaxane counterpart was also synthesized under similar conditions. The chemical structures of these compounds were evidenced by using ATR-FT-IR and WAXS. The thermal stability was evaluated by TGA analysis. The evolution of dielectric constant and dielectric loss by varying the temperature and frequency, and conductivity of the investigated compounds were compared with those of the pure cross-linked material. The value of the dielectric constant of pure cross-linked film at 10 Hz frequency is 2.6, whereas for the film with PEDOT-βCD polyrotaxane incorporated into the matrix increases to 32, which are consistent with the dielectric loss and conductivity results. At the lower temperature region, the alternating current conductivity ( σ AC ) increases monotonically with increasing of frequency, denoting that the conductivity of short-range species is predominant. When the temperature increases, the direct current conductivity ( σ DC ), corresponding to the long-range mobility of the free charges is independent of the frequency.